Solution:
Given: \theta = 60°
To prove: cos3\theta = 4cos^3 \theta - 3cos\theta
We know,
cos 60° = \dfrac{1}{2}
cos(90° + \theta) = - sin \theta
sin 90° = 1
Taking LHS
= cos 3\theta
= cos(3\theta)
= cos(3×60°)
= cos(180°)
= cos(90°+90°)
= - sin90°
= - 1 [or you can use calculator]
Taking RHS
= 4cos^3 \theta - 3cos\theta
= 4(cos \theta)^3 - 3cos\theta
= 4(cos 60°)^3 - 3cos60°
= 4 \left ( \dfrac{1}{2} \right )^3 - 3× \dfrac{1}{2}
= 4× \dfrac{1}{8} - \dfrac{3}{2}
= \dfrac{1}{2} - \dfrac{3}{2}
= \dfrac{1 -3}{2}
= \dfrac{-2}{2}
= -1
Since, LHS = RHS
cos3\theta = 4cos^3 \theta - 3cos\theta #proved
#SciPiPupil
#Trigonometry
0 Comments
You can let us know your questions in the comments section as well.